Les séries ludiques en argot et en langue familière : saut métaphorique et rebond - Fabrice Antoine (Lexis: Journal in English Lexicology)
Building on the idea of a “word-creator”, a lexical machine that combines semantic devices like metaphor and metonymy and formal devices (mainly borrowed from Tournier’s lexicogenic devices) to produce new lexical items, a process that is especially observable in slang and colloquial language, both in English and in French, this paper focuses on series of synonymous slang and colloquial language words and expressions. Some of these are built around what we call a “semantic equation”, or a semantic trait that is brought into sharp focus. Other sets of expressions, which are much larger, are built around the iteration and slight deformation of a prototypical expression that ends up being forgotten in the rather mechanical re-use of the expression’s general outline. It is argued here that this mechanism illustrates the notion of slang as wordplay as the expressions thus created seem to echo one another over time and to build upon one another in a sort of attempt at being funnier, or more original or more absurd than those who came before.